3D spatial organization and improved antibiotic treatment of a Pseudomonas aeruginosa–Staphylococcus aureus wound biofilm by nanoparticle enzyme delivery - Rubio-Canalejas, Alba; Baelo, Aida; Herbera, Sara; Blanco-Cabra, Núria; Vukomanovic, Marija; Torrents, Eduard (Frontiers in Microbiology, 2022)
Chronic wounds infected by Pseudomonas aeruginosa and Staphylococcus aureus are a relevant health problem worldwide because these pathogens grow embedded in a network of polysaccharides, proteins, lipids, and extracellular DNA, named biofilm, that hinders the transport of antibiotics and increases their antimicrobial tolerance. It is necessary to investigate therapies that improve the penetrability and efficacy of antibiotics. In this context, our main objectives were to study the relationship between P. aeruginosa and S. aureus and how their relationship can affect the antimicrobial treatment and investigate if functionalized silver nanoparticles can improve the antibiotic therapy. We used an optimized in vitro wound model that mimics an in vivo wound to coculture P. aeruginosa and S. aureus biofilm. The in vitro wound biofilm was treated with antimicrobial combinatory therapies composed of antibiotics (gentamycin and ciprofloxacin) and biofilm-dispersing free or silver nanoparticles functionalized with enzymes (α-amylase, cellulase, DNase I, or proteinase K) to study their antibiofilm efficacy. The interaction and colocalization of P. aeruginosa and S. aureus in a wound-like biofilm was examined and detailed characterized by confocal and electronic microscopy. We demonstrated that antibiotic monotherapy is inefficient as it differentially affects the two bacterial species in the mixed biofilm, driving P. aeruginosa to overcome S. aureus when using ciprofloxacin and the contrary when using gentamicin. In contrast, dual antibiotic therapy efficiently reduces both species while maintaining a balanced population. In addition, DNase I nanoparticle treatment had a potent antibiofilm effect, decreasing P. aeruginosa and S. aureus viability to 0.017% and 7.7%, respectively in combined antibiotics. The results showed that using nanoparticles functionalized with DNase I enhanced the antimicrobial treatment, decreasing the bacterial viability more than using the antibiotics alone. The enzymes α-amylase and cellulase showed some antibiofilm effect but were less effective compared to the DNase I treatment. Proteinase K showed insignificant antibiofilm effect. Finally, we proposed a three-dimensional colocalization model consisting of S. aureus aggregates within the biofilm structure, which could be associated with the low efficacy of antibiofilm treatments on bacteria. Thus, designing a clinical treatment that combines antibiofilm enzymes and antibiotics may be essential to eliminating chronic wound infections.